Overweight and obesity categories of residents in a local urban area - Tshalibe, Rumbidzai S.; Ndlovu, Nomagugu; Usai, Tecklah.; Makamure, Charlotte; Chinofunga, Dorothy; Mutonhodza, B.; Kawadza, S.T. (IOSR journal of environmental science, toxicology and food technology, 2016)
The purpose of this study was to determine the applicability of the WHO categories of overweight and obesity in Gweru residents. Measurements of body mass index (BMI), waist circumference and skin fold were carried out. The manifestation of either hypertension, type 2 diabetes or both in individuals were self reported. Findings revealed that hypertension and Type 2 diabetes were prevailing at significantly higher BMI categories in Gweru residents. The number of individuals who were obese was significantly higher posing them at an increased risk of the consequences sooner or later. The researcher recommends intervention that will increase the population’s awareness on how to prevent obesity.